Manajemen Pengelolaan Sampah di Kota Serang - Ni’mattulah Ni’mattulah; Agus Sjafari; Riswanda Riswanda (JURNAL MANAJEMEN AGRIBISNIS, 2022)
Dump removal has been a remaining issue in Serang, the capital city of Banten Province. Domestic waste could be seen on some side roads over illegal dumping. The local government comes out with a yet-to-be proper responds to the problem. This study aims at assessing the implementation and waste management based on the law no 10 year 2012 concerning waste management in the City. The research aproach is descriptive qualitative underpinning critical systemic thinking paradigm. This study adapts Van Metter Van Horn policy model to frame the issue. The findings indicate that the waste management policy needs to be reconstructed in terms of budgeting and resources. Relocating and redistributing are vital to network all stakeholders related to the waste management issue. Public communication and public education are a necessity given the dump removal issue has long been dominated by government lenses, excluding those at the receiving ends of the policy.